Microelectronics / Second Edition - Grabel Arvin; Millman Jacob (Mcgraw Hill Book Company, 1987)
Preface, A Brief History of Electronics, Semiconductor Devices, Semiconductors, The PN Junction Diode, Biopolar Junction Transistors, Field-Effect Transistors, Integrated-Circuit Fabrication, Digital Circuits and Systems, Basic Logic (Digital) Circuits, Combinatorial Digital Circuits, Sequential Circuits and Systems, Very Large Scale Integrated Systems, Amplifier Circuits and Systems, Basic Amplifier Stages at Low Frequencies, Frequency Response of Amplifiers, Feedback Amplifiers, Stability and Response of Feedback Amplifiers, Operational-Amplifier Characteristics, Signal Processing and Data Acquisition, Waveform Generators and Waveshaping, Signal Conditioning and Data Conversion, Large-Signal Electronics, Power Circuits and Systems, Appendices, Index.